Improving Robustness of Neural Dialog Systems in a Data-Efficient Way with Turn Dropout - Shalyminov, Igor; Lee, Sungjin (The Thirty-second Annual Conference on Neural Information Processing Systems (NIPS) 2018, workshop on Conversational AI: “Today's Practice and Tomorrow's Potential, 2018)
Neural network-based dialog models often lack robustness to anomalous, out-of-domain (OOD) user input which leads to unexpected dialog behavior and thus considerably limits such models' usage in mission-critical production environments. The problem is especially relevant in the setting of dialog system bootstrapping with limited training data and no access to OOD examples. In this paper, we explore the problem of robustness of such systems to anomalous input and the associated to it trade-off in accuracies on seen and unseen data. We present a new dataset for studying the robustness of dialog systems to OOD input, which is bAbI Dialog Task 6 augmented with OOD content in a controlled way. We then present turn dropout, a simple yet efficient negative sampling-based technique for improving robustness of neural dialog models. We demonstrate its effectiveness applied to Hybrid Code Networks (HCNs) on our data. Specifically, an HCN trained with turn dropout achieves more than 75% per-utterance accuracy on the augmented dataset's OOD turns and 74% F1-score as an OOD detector. Furthermore, we introduce a Variational HCN enhanced with turn dropout which achieves more than 56.5% accuracy on the original bAbI Task 6 dataset, thus outperforming the initially reported HCN's result.